Соціально-економічні тенденції розвитку нутріївництва - Павленко, Оксана Павлівна; Pavlenko, Oksana (Дніпровський державний аграрно-економічний університет, 2015)
Розкрито історичний аспект розвитку нутріївництва. Проаналізовано виробництво галузі за видами продукції, світовий досвід та особливості даного виду аграрного бізнесу. Розглянуто основні якісні характеристики продукції та вплив її на організм людини, основні переваги та проблеми подальшого розвитку нутріївничих підприємств. The article deals with the historical aspect of nutria farming, analyzed by manufacturing industry products, international experience and characteristics of this type of agricultural business, the basic qualitative characteristics of products and its impact on the human body, the main advantages and problems of further development nutria’s enterprises. Reflects the main elements of the socio-economic system of the industry, defined the resource potential of the genesis of the region, including a diversified production structure and social preconditions for the development of agro-industrial complex of the country. The problems of development of the meat and fur nutria’s enterprises, identified positive aspects and risks of this type of business, are proposals to increase competitiveness. The analysis of the historical development and innovation processes, which are aimed at improving the production, storage, processing and sales. The main impediments to innovation activity are underdeveloped innovation and information infrastructure, lack of qualified personnel, lack of financial resources. In the current situation, problems of socio-economic development nutria’s enterprises are relevant and increasing the efficiency of the industry makes it possible to accelerate the development of livestock and the provision of alternative high-quality products.
Socio-economic trends оf nutria farming
Keywords: нутріївництво; nutria farming; історичний досвід; historical experience; виробництво м’ясної продукції; the production of meat products; хутросировина; fur farming; інтеграція; integration; ринкова інфраструктура; market infrastructure; соціально-економічний розвиток; socio-economic development